Integrasi kurikulum Nasional dan Cambridge Primary di SD laboratorium UM: Analisis dokumen kurikulum dan implementasinya - Azza, Himawan Aufaqil; alfiatun nafi’ah, Shabrina Yudhitia; Amelia, Dinda Dwi Riski (Maliki Interdisciplinary Journal, 2025)
This study examines the integration of the National Curriculum and the Cambridge Primary Curriculum at SD Laboratorium UM through curriculum document analysis and classroom implementation review. The integration aims to meet 21st-century competency demands by combining national standards with international approaches. The research employs document analysis and observations of learning practices in English, Math, and Science. The findings indicate that curriculum integration is carried out through competency mapping between the two curricula, resulting in bilingual teaching materials. Learning is implemented using active and collaborative approaches, with English as the main medium of instruction for Cambridge subjects. Assessment combines national evaluations with Cambridge assessments such as Progress Checks and Checkpoint examinations. The integration improves students’ English proficiency, numeracy skills, and scientific literacy, although challenges remain, including limited Cambridge materials and teacher readiness. Overall, this integrated model contributes positively to enhancing the quality of primary education.